Comparison of efficacy and safety of zinc gluconate versus placebo for treatment of Primary Dysmenorrhea - Faiza Safdar, Shabana Kalsoom, Noreen Majeed, Khairun Nisa, Mamoona Riaz, Shamsa Tariq (Journal of Rawalpindi Medical College, 2022)
Background & Objectives: Dysmenorrhea is a common gynecological complaint in women of reproductive age. Primary dysmenorrhea is defined as painful menstruation in the absence of any pelvic pathology and occurs in response to increased prostaglandin release from the ischemic endometrium. Conventional treatments include NSAIDs and oral contraceptive pills. Zinc is an essential micronutrient with anti-inflammatory properties. We conducted this study to evaluate the efficacy and safety of zinc supplementation in treatment of primary dysmenorrhea in our target population as it presents as very common gynaecological issue in young adolescents females. Methods: 100 participants with primary dysmenorrhea were enrolled in study from outpatient department via non-probability consecutive sampling. They were randomized into two groups. The intervention group (Group A) received zinc gluconate 50mg once daily and the control group (Group B) received placebo drug once daily, for 5 days before and 2 days after onset of menstruation. After three and six months of treatment severity of primary dysmenorrhea was assessed and compared in both groups using visual analogue scale for pain, along with side effect profile. Results: The treatment with Zinc gluconate reduced the mean pain score in females with primary dysmenorrhea after 3months with a further reduction after 6 months of treatment (P<0.001) as compared to placebo. Very few (4% after 3 months & 6% after 6 months) participants experienced the side effects of Zinc supplementation. Conclusion: zinc gluconate 50mg daily for 5 days before and 2 days after onset of menstruation can effectively treat the primary dysmenorrhea. The drug has very few side effects at this dose and duration of use. Key words: Primary dysmenorrhea, zinc gluconate, pain severity, visual analogue scale.